Mini Grids for Half a Billion People : Market Outlook and Handbook for Decision Makers - Energy Sector Management Assistance Program (World Bank, Washington, DC, 2019)
Approximately 1.2 billion people will need to gain access to electricity to achieve universal access by 2030. The only way to achieve this is through a combination of the main grid extension, mini grids, and off-grid solar. This report shows that about half a billion people can be cost-effectively provided with electricity through mini grids. The combination of falling costs, dramatic increase in the quality of service, and favorable enabling environments have made modern mini grids a scalable option to complement grid extension and solar home systems. The report is the most comprehensive study on mini grids to date. It takes stock of the global mini grid market and industry; analyzes in detail the solar-hybrid mini grid costs and technological innovations; shows the importance of introducing income-generating machinery and micro-finance early in the planning process; and provides policy makers, investors and developers with insights on how mini grids can be scaled up. Modern mini grids can pave the way for more financially viable future grid expansion, as by the time the main grid arrives, significant demand for electricity already exists and customers have a greater ability to pay. The key is to define—in advance—technical standards and commercial options for integration once the main grid arrives. A win-win situation for both the mini grid developers and national utilities. Mini grids are not a new phenomenon: nearly all electricity grid systems in high-income countries started with isolated mini grids, which gradually interconnected. Over the past several decades throughout the rest of the world, mini grids have grown from a niche solution for electrification to being deployed widely. Globally, at least 19,000 mini grids are installed in 134 countries, representing a total investment of 28 billion US Dollars and providing electricity to about 47 million people. Asia has the most mini grids installed today, while Africa has the largest share of planned mini grids. However, at present, the combined mini grid investment in countries with low levels of electricity access in Africa and Asia totals only 5 billion US Dollars, compared to the 220 billion US Dollars needed to connect 500 million people to 210,000 mini grids in these regions by 2030. Therefore, across the globe, countries need to actively mobilize private sector investment. This can be achieved by setting up policies that support comprehensive electrification programs, promoting viable business models, and providing well-designed public funding, for example through performance-based grants.